Peranan Maahad Tahfiz Ad-Din Dalam Melahirkan Huffaz di Negeri Perak Darul Ridzuan (Sains Humanika, 2018)
This study aims to evaluate the role of Maahad Tahfiz ADDIN to produce huffaz in the State of Perak Darul Ridzuan based on the implementation of the Tahfiz Al-Quran curriculum with important instruments of collecting quantitative data (questionnaires). A survey method which was used involved 366 students from the Maahad Tahfiz Al-Quran ADDIN in the state of Perak who are randomly selected. The subjects of the study were students aged 13 years to 17 years old. A questionnaire was developed to collect the required data. The findings were analyzed descriptively by Statistical Package for Social Sciences (SPSS) Version 22.0. The results show that the implementation of the goals and objectives of the Quranic Tahfiz curriculum at Maahad Tahfiz ADDIN was the highest mean of 3.60. The conclusions from this study show that the goal and objectives of tahfiz are at a good level and can be further enhanced. On the other hand, the content of the curriculum and time allocation for the Quranic memorization should be given due attention and improvements so that Maahad Tahfiz ADDIN can actually filling the gap in producing more quality huffaz in the state of Perak Darul Ridzuan.
Keywords: Curriculum; goal; tahfiz al-Quran; huffaz; Maahad Tahfiz ADDIN